Thermal field visualization of nanofluids using full-field interferometry. (July 2015) - Yousefi, T.; Farahbakhsh, B.; Naylor, D.; Saghir, M.Z.
Abstract: This paper reports the visualization of the temperature field in light-transmitting nanofluids using a Mach–Zehnder interferometer. In this study, the evolution of the free convective temperature fields around a resistively heated vertical metal strip was observed in two nanofluids. Visualization has been obtained using a 15 mW He-Ne laser (632.8 nm) for SiO2 –water and Al2 O3 –water nanofluids over a range of concentrations. The optical path length of the test beam through the nanofluid was 7 mm. The results show that a SiO2 –water nanofluid can be used up to a concentration of at least 40% by weight. Al2 O3 –water nanofluid can be used up to at least 1% concentration by weight, provided the solution is adequately homogenized. This work demonstrates that optical temperature field and the local heat flux measurements are technically feasible in these nanofluids.